Topology Optimization of Textured Journal Bearings - Hanqian Kong; Chunxing Gu; Di Zhang; Lanfei Wu (Lubricants, 2025)
The journal bearing, a critical component of the rotating shaft, is influenced by various factors including friction, wear, and heat effects under actual working conditions. This study developed an advanced approach for optimizing the performance of journal bearings with surface texture. This approach allows for finding the influences of bearing parameters such as journal clearance, rotational speed, and shaft eccentricity ratio on the optimization results. The results show that whether under smaller journal clearances, higher rotational speeds, or larger shaft eccentricity ratios, the formation of intricate bifurcation patterns and enhanced branching in surface textures is consistently promoted. The optimized texture’s shape leads to a reduction in texture depth while significantly improving both the load-carrying capacity (LCC) and oil film thickness. This approach precisely determines the spatial and depth characteristics of texture elements, ensuring their optimal placement and geometry, and offers valuable insights and directions for future research.